Preparation and characterization of a novel magnetic biochar for arsenic removal - Zhang, Ming; Gao, Bin; Varnoosfaderani, Sima; Hebard, Arthur; Yao, Ying; Inyang, Mandu (Bioresource technology, 2013)
[Display omitted] ► A magnetic biochar can be fabricated via pyrolysis of FeCl3 treated biomass. ► Colloidal or nanosized γ-Fe2O3 particles grow within biochar matrix. ► Biochar/γ-Fe2O3 composite has excellent ferromagnetic properties. ► Biochar/γ-Fe2O3 composite has strong sorption ability to As(V). A magnetic biochar based adsorbent with colloidal or nanosized γ-Fe2O3 particles embedded in porous biochar matrix was fabricated via thermal pyrolysis of FeCl3 treated biomass. The synthesized samples were studied systematically by X-ray diffraction, X-ray photoelectron spectroscopy, transmission electron microscopy, selected-area electron diffraction pattern, scanning electron microscopy, energy-dispersive X-ray analysis, superconducting quantum interference device, and batch sorption measurements. The characterization analyses showed that large quantity of γ-Fe2O3 particles with size between hundreds of nanometers and several micrometers tightly grow within the porous biochar matrix. Biochar/γ-Fe2O3 composite exhibited excellent ferromagnetic property with a saturation magnetization of 69.2emu/g. Batch sorption experimental results showed that the composite has strong sorption ability to aqueous arsenic. Because of its excellent ferromagnetic properties, the arsenic-laden biochar/γ-Fe2O3 composite could be easily separated from the solution by a magnet at the end of the sorption experiment.